Power frequency magnetic field from A 275 KV GIS substation in Malaysia - Hussain H.; Farag A.S.; Said I.B.; Rahman N.A. (2023)
Gas insulated substations (GIS) have received much consideration from utilities and are preferred for service in urban areas due to its compactness. Consequently, for concerned utilities it is important to address the issue of environmental conditions in and around their GIS. One of which is the issue of magnetic field exposures which have drawn a great deal of attention recently due to its possible health hazards. This paper presents the results of measurements of the power frequency magnetic fields on a 275 kV GIS substation in Malaysia. The measurements carried out covers the magnetic field from substation equipment, the in-coming and out-going power lines and cables to and from the substation. Substation loading at the time of measurement were recorded. Results obtained were presented in various formats such as linear, contour and three-dimensional plots. Statistical representation of the measured data showing the minimum, maximum, mean, standard deviation and median magnetic field for all measured areas were presented. Based on the results, the main sources of magnetic fields within the substation were identified. Results from the measurements will be used as raw data for future simulations and case studies on the substation. 2004 IEEE.